2012
DOI: 10.1371/journal.pone.0033243
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intestinal Adenoma Formation in APCMin/+ Mice by Riccardin D, a Natural Product Derived from Liverwort Plant Dumortiera hirsuta

Abstract: BackgroundMutation of tumor suppressor gene, adenomatous polyposis coli (APC), is the primary molecular event in the development of most intestinal carcinomas. Animal model with APC gene mutation is an effective tool for study of preventive approaches against intestinal carcinomas. We aimed to evaluate the effect of Riccardin D, a macrocyclic bisbibenzyl compound, as a chemopreventive agent against intestinal adenoma formation in APCMin/+ mice.Methods APCMin/+ mice were given Riccardin D by p.o. gavage for 7 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…NF-κB, a proinflammatory transcription factor, functions as the 'first responder' to various generators of cellular stress, including free radicals and pro-inflammatory cytokines (e.g. TNF-α) and bacterial biomolecules) (27). In the present study, H 2 O 2 was observed to induce an inflammatory response involving NF-κB and its associated signals.…”
Section: Discussionmentioning
confidence: 47%
“…NF-κB, a proinflammatory transcription factor, functions as the 'first responder' to various generators of cellular stress, including free radicals and pro-inflammatory cytokines (e.g. TNF-α) and bacterial biomolecules) (27). In the present study, H 2 O 2 was observed to induce an inflammatory response involving NF-κB and its associated signals.…”
Section: Discussionmentioning
confidence: 47%
“…Colorectal cancer (CRC) is one of the leading causes of cancer mortalities worldwide, and is the third most common cancer type and the fifth leading cause of mortality in China ( 1 3 ). The majority of CRCs develop sporadically (70–80%), and the somatic loss of tumor suppressor gene, adenomatous polyposis coli ( APC ), was revealed to be present in 85% of patients with CRC and familial adenomatous polyposis ( 4 6 ). It has previously been demonstrated to have significant pro-apoptosis and anti-proliferative effects in several different types of cancers in vivo and in vitro ( 1 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…This liverwort has a thin with the dark green color thallus, flat margin, and papilla on the rhizoid. D. hirsuta produces secondary metabolites called Riccardin D which can inhibit the growth of tumor cells (Liu et al, 2012). (Lee et al, 1977) Anthoceros punctatus Anthocerotaceae Agriculture (mychorrhiza) (Schüßler, 2000) Barbula javanica Pottiaceae Decorative plant, medicinal plant (antimicrobial) (Schenk, 1997); (Singh et al, 2007); (Vats & Alam, 2013) Bazzania sp.…”
Section: Resultsmentioning
confidence: 99%
“…(Lee et al, 1977) Anthoceros punctatus Anthocerotaceae Agriculture (mychorrhiza) (Schüßler, 2000) Barbula javanica Pottiaceae Decorative plant, medicinal plant (antimicrobial) (Schenk, 1997); (Singh et al, 2007); (Vats & Alam, 2013) Bazzania sp. Lepidoziaceae Medicinal plant (antimicrobial) (Alam et al, 2015) Brachymenium nepalense Bryaceae Antimicrobial; medicinal plant ; (Wankhede & Manik, 2015) Bryum billardieri Bryaceae Decorative plant (Schenk, 1997) Campylopus crispifolius Dicranaceae Decorative plant (Schenk, 1997) Campylopus micholitzii Dicranaceae Decorative plant (Schenk, 1997) Campylopus umbellatus Dicranaceae Decorative plant (Schenk, 1997) Cyathodium foetidissimum Targioniaceae Fragrance; fixative plant (Allen et al, 2017) Dicranoloma reflexum Dicranaceae Decorative plant, medicinal plant (Junairiah et al, 2016) Dumortiera hirsuta Marchantiaceae Medicinal plant (antitumor) (Liu et al, 2012) Ectropothecium ichnotocladum Hypnaceae Decorative plant (Schenk, 1997); (Glime, 2013) Fissidens crassinervis Fissidentaceae Medicinal plant (antibacterial) (Glime, 2013) Fissidens javanicus Fissidentaceae Medicinal plant (antibacterial) (Glime, 2013) Frullania sp. Jubulaceae Medicinal plant (antibacterial, anti-cancer) (Glime, 2013); (Asakawa, 2007) Heteroscyphus argutus Geocalycaceae Medicinal plant (anticancer) (Lin et al, 2012) Hyophila involuta Pottiaceae Medicinal plant (antibacterial); ecocity (Glime, 2013); (Singh et al, 2016) Hypnodendron sp.…”
Section: Resultsmentioning
confidence: 99%